PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA PEMBELAJARAN IPAS KELAS IV SD - Amanda Sari, Ultari; Ulya Akmal, Atika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the limited use of technology-based instructional mediain elementary-level science and social studies (IPAS) learning, particularly for thetopic of changes in the states of matter a subject that students commonly perceiveas abstract and difficult to grasp. Accordingly, this study aimed to build anAugmented Reality (AR) learning tool for fourth-grade IPAS instruction that satisfiesthe criteria of validity, practicality, and effectiveness. A Research and Development(R&D) design was applied, following the five phases of the ADDIE frameworkAnalysis, Design, Development, Implementation, and Evaluation. Participants werefourth-grade students from SDN 14 Koto Lalang, SDN 05 Kapalo Koto, and SDN 30Cengkeh, with data collected through expert validation sheets, practicalityquestionnaires, and pretest–posttest scores. Findings show that the AR toolachieved a high level of validity, scoring 82% for content, 98% for language, and90% for media design, for an overall average of 90% (very valid). Teachers andstudents alike gave highly favorable responses in the practicality trial, placing thetool in the highly practical category. The effectiveness trial yielded an average NGain of 0.46, a moderate figure indicating that the tool meaningfully improvedlearning outcomes. Overall, the AR-based learning tool met the standards of validity,practicality, and effectiveness, making it a workable alternative resource for teachingthe states-of-matter topic in fourth-grade IPAS.